(−)‑Epigallocatechin‑3‑O‑gallate upregulates the expression levels of miR‑6757‑3p, a suppressor of fibrosis‑related gene expression, in extracellular vesicles derived from human umbilical vein endothelial cells. Issue 3 (2023) - Murata, Motoki; Marugame, Yuki; Morozum, Mai
No abstract available